A new simplified meta-model to evaluate the transmission of ground movements to structures integrating the elastoplastic soil behavior. (February 2020) - El Kahi, Elio; Deck, Olivier; Khouri, Michel; Mehdizadeh, Rasool; Rahme, Pierre
Graphical abstract: Highlights: Propose simplified meta-models to evaluate (Δ/Δ0 )Elastic for Winkler & Pasternak. Incorporate elastoplastic conditions in elastic models using the soil bearing capacity. Elastoplastic Δ/Δ0 equations using ANN that can be used by engineers and designers. Abstract: Many buildings may suffer damage due to ground movements associated to underground excavations like tunneling, mines or urban excavations. The level of damage depends upon the rate of ground movements transmitted to structures that is affected by the soil-structure interaction (SSI) conditions and parameters such as the soil elastoplastic behavior. The purpose of this paper is to integrate the soil elastoplasticity while investigating the response of a structure sitting on a soil subjected to a ground movement. Analytical and numerical approaches are applied to examine the effect of the non-linear soil behavior. The analytical approach is based on modified Winkler and Pasternak elastic models under the assumption of limiting the soil reaction by its bearing capacity; the numerical approach is based on finite element models, using Plaxis 2D that consider an elastoplastic soil behavior. Results display the discrepancy in the structural response between considering an elastic or an elastoplastic soil behavior. Based on a significant number of iterations, the artificial neural network technique is used to propose a new simplified meta-model that integrates the soil elastoplasticity to evaluate the transmission of ground movements to structures. In addition, a procedure, which can be used by engineers and designers, is developed to evaluate the transmission ratio for any structure sitting on any type of soil.